Large-lamellar MXene material as well as preparation method and application thereof
Through the mechanical stirring stress shear peeling method, the problems of uniformity and low efficiency in eddy current shear peeling are solved, and high-quality large-sheet MXene is obtained, which realizes industrial mass production and excellent electromagnetic shielding performance.
Patent Information
- Application Number
- CN202411467414.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the eddy current shear peeling method is difficult to obtain high-quality large single layer MXene evenly and efficiently, and it is easy to damage the sheet layer, affecting the application of the material.
The mechanical stirring stress shear peeling method is adopted to generate high-intensity shearing force when rotating through the crescent-shaped stirring paddle, forming a turbulent area, overcoming the van der Waals force between the MXene sheets, and achieving uniform peeling.
The preparation of high-yield and high-quality large-sheet MXene material has been achieved, with an average lateral dimension of more than 4.2μm, and the material has excellent performance in the field of electromagnetic shielding, with an SSE/t value of more than 38161.
Smart Images

Figure CN119284906A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterial preparation, and specifically relates to a large-sheet MXene material, a preparation method and application thereof. Background Art
[0002] MXene is a new type of two-dimensional nanomaterial with excellent performance, two-dimensional layered structure of metal carbides or nitrides and a large family. These new two-dimensional materials have broad application prospects in various fields such as energy storage, catalysis, superconductivity, and electromagnetic shielding. In 2014, Ghidiu et al. used lithium fluoride (LiF) and hydrochloric acid (HCl) as etching reagents and lithium ions (Li + ) as an intercalant to fill and expand Ti3C2T x The exfoliation yield can reach 45%. In the research on mass production of MXenes, there are only a few companies that have attempted large-scale production to prepare single-layer Ti3C2T x MXenes almost all rely heavily on ultrasonic exfoliation. However, due to the difficulty in scaling up the preparation process and the laboratory process for large-scale exfoliation, currently reported methods such as repeated freeze-thaw method and supercritical technology cannot be applied industrially.
[0003] In 2023, Daping He et al. used eddy shear exfoliation to exfoliate multilayer MXene to obtain single-layer MXene by relying on the eddy shear force generated by the eddy region naturally formed by the flow of liquid in a shaker, with a yield of up to 90%. However, in eddy shear, the formation of the vortex region is mainly caused by the change in the velocity gradient of the fluid in the boundary layer. The formation of this shear force is the result of natural fluid movement, and its intensity and distribution are limited by the scale of the vortex and the characteristics of the fluid. Since the shear force is concentrated in the local eddy region, problems such as incomplete flaky exfoliation or local over-exfoliation will occur, and the single-layer MXene is prone to re-aggregation under the action of the vortex, affecting the exfoliation quality and efficiency. Therefore, eddy shear exfoliation is uneven or easily damages the flaky layer, making it difficult to obtain high-quality large-layer single-layer MXene, affecting the subsequent application of the material. Therefore, a new method is needed to efficiently and uniformly obtain high-quality large-layer single-layer MXene. Summary of the invention
[0004] The main purpose of the present invention is to provide a large-sheet MXene material, a preparation method and application thereof, so as to overcome the deficiencies in the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: One aspect of the present invention provides a method for preparing a large-sheet MXene material, comprising: Etching the MAX phase material with an etchant to obtain a multilayer MXene material; The multilayer MXene material is dispersed in a dispersion medium and subjected to mechanical stress shear exfoliation to obtain a large-sheet MXene material, wherein the average lateral size of the large-sheet MXene material is greater than 4.2 μm.
[0006] Another aspect of the present invention provides a large-sheet MXene material prepared by the aforementioned preparation method, wherein the average lateral size is greater than 4.2 μm.
[0007] Another aspect of the present invention also provides a MXene film, which is formed by the aforementioned large-sheet MXene material.
[0008] Another aspect of the present invention also provides the application of the aforementioned large-sheet MXene material or the aforementioned MXene film in the field of electromagnetic absorption and shielding.
[0009] Compared with the prior art, the technical solution of the present invention has at least the following advantages: 1) The mechanical stirring stress shearing peeling method provided by the present invention can peel off large-sheet MXene materials with an average lateral size of more than 4.2 μm at a high yield, with high product quality and large yield, which is conducive to industrial mass production; 2) The MXene film made of the large-sheet MXene material provided by the present invention has excellent electromagnetic shielding ability, and the SSE / t value is between 38161 The above can be widely used in the field of electromagnetic absorption and shielding. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0011] Figure 1 This is the SEM image of the MXene material prepared in Example 1; Figure 2 This is a particle size distribution diagram of the MXene material prepared in Example 1; Figure 3 This is the XRD pattern of the MXene material prepared in Example 1; Figure 4 This is a photo of the MXene material (solution) prepared in Example 1; Figure 5This is the SEM image of the MXene material prepared in Example 2; Figure 6 This is the particle size distribution diagram of the MXene material prepared in Example 2; Figure 7 This is the SEM image of the MXene material prepared in Example 3; Figure 8 This is the particle size distribution diagram of the MXene material prepared in Example 3; Fig. 9 This is the SEM image of the MXene material prepared in Example 4; Fig.10 This is the particle size distribution diagram of the MXene material prepared in Example 4; Fig.11 This is a SEM image of the MXene material prepared in Example 5; Fig.12 This is a particle size distribution diagram of the MXene material prepared in Example 5; Fig.13 Schematic diagram of the stress of liquid in a mechanical stirring device at different rotation speeds in a typical embodiment of the present invention. DETAILED DESCRIPTION
[0012] The present invention will be more fully understood by reading the following specific embodiments. However, it should be understood that the specific embodiments disclosed below are only exemplary of the present invention, and the present invention can be embodied in various forms. Therefore, the specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.
[0013] As one aspect of the technical solution of the present invention, a method for preparing a large-sheet MXene material includes: Etching the MAX phase material with an etchant to obtain a multilayer MXene material; The multilayer MXene material is dispersed in a dispersion medium and subjected to mechanical stress shear exfoliation to obtain a large-sheet MXene material, wherein the average lateral size of the large-sheet MXene material is greater than 4.2 μm.
[0014] In some embodiments, the preparation method comprises: performing the mechanical stress shear peeling with a mechanical stirring device; the mechanical stirring device comprises a stirring paddle.
[0015] In some preferred embodiments, the blade of the stirring paddle is a crescent-shaped blade. When the crescent-shaped blade rotates, forces are applied in radial and axial directions at the same time. This design causes the liquid to generate high-intensity shear force around the stirrer. In addition, strong stress concentration is generated at the tip of the crescent during stirring and rotation. This complex flow pattern can form a turbulent area in the stirring system, increasing the collision frequency between particles in the liquid and the stirring paddle. This multi-directional flow and turbulence effect improves the stripping efficiency and ensures the uniformity of the stripping process.
[0016] In some preferred embodiments, the diameter of the blade of the stirring paddle is 1 / 3-1 / 2 of the inner diameter of the container.
[0017] In some preferred embodiments, the rotation speed of the stirring paddle is 500-2000 rpm.
[0018] In some preferred embodiments, the mechanical stress shear peeling time is 5-120 min.
[0019] The present invention generates shear force in a multilayer MXene solution by rotating a mechanical stirring paddle, thereby peeling off the multilayer MXene to obtain a single layer of MXene. The rotation of the mechanical stirring paddle introduces a strong shear force through the relative movement between the blade and the liquid, overcoming the van der Waals force between the MXene sheets, so that the multilayer MXene is gradually peeled off into a single layer.
[0020] For details, please refer to Fig.13 , Fig.13 is a schematic diagram of the stress of the liquid in the mechanical stirring device at different rotation speeds in a typical embodiment of the present invention, wherein V max It is the maximum flow rate in the stress concentration area generated by mechanical stirring. In the stripping process of the present invention, the shear force is directly generated by the blades of the stirring paddle, and the intensity and distribution can be precisely controlled by the design (such as shape, size) and rotation speed of the stirring paddle blades. The continuous shear force provided by the stirring paddle can strip multilayer MXene more efficiently. The shear force of mechanical stirring covers the entire flow field, is evenly distributed and has high intensity, and can evenly strip MXene in the entire solution, so that the stripping efficiency is high and the monolayer yield is good. The rotation of the mechanical stirring paddle also induces turbulence and micro-eddies. These flow disturbances increase the mixing efficiency of the liquid and form a multi-directional shear stress field, thereby further enhancing the stripping effect. The turbulence and continuous multi-directional shear stress field enable the monolayer MXene to be quickly dispersed in the solution, effectively preventing the re-aggregation of the monolayer sheets after stripping, and ensuring the stability and uniformity of the monolayer.
[0021] In some embodiments, the MAX phase materials include but are not limited to Ti3AlC2, Ti2AlC, Ti3AlN2, Ti2AlN, Ti3AlCN, Ti4AlN3, Ti2VAlC2, TiVAlC, TiNbAlC, Ti3GeC2, Ti3SiC2, Ti2SnC, V2AlC, V3AlC2, V4AlC3, VNbAlC, VCrAlC, V2GeC, V2GaC, V2ZnC, V2PC, Nb4AlC3, Nb3AlC2, Nb2A1C, Cr2AlC, Cr2GaC, Mo3AlC2, Mo2GaC, Mo2Ga2C, Mo2Ti2AlC3, Mo2TiAlC2, (Mo 2 / 3 Sc 1 / 3 )2AlC、(Mo 2 / 3 Y 1 / 3 )2AlC, Ta4AlC3, Ta3AlC2, Ta2AlC, (W 2 / 3 Y 1 / 3 )2AlC、(W 2 / 3 Sc 1 / 3 )2AlC any one or a combination of two or more.
[0022] In some embodiments, the preparation method comprises: adding the MAX phase material to the etchant, stirring at 50-85° C. for 24-72 hours, and centrifuging to obtain the multilayer MXene material.
[0023] In some preferred embodiments, the etchant comprises an acidic solution containing a fluoride salt.
[0024] In some more preferred embodiments, the fluoride salt includes but is not limited to any one of LiF and NaF or a combination of both.
[0025] In some more preferred embodiments, the acidic solution includes but is not limited to hydrochloric acid.
[0026] In some more preferred embodiments, the acid concentration in the acidic solution is 9-12 mol / L.
[0027] In some more preferred embodiments, the mass volume ratio of the MAX phase material, the fluoride salt and the acidic solution is (3-10) g: (4.8-16) g: (60-200) mL.
[0028] In some embodiments, the preparation method further comprises: washing the multilayer MXene material by centrifugation until it becomes neutral and then dispersing the material in a dispersion medium.
[0029] In some preferred embodiments, the dispersion medium includes, but is not limited to, any one of water, dimethyl sulfoxide (DMSO), and N-methylpyrrolidone (NMP), or a combination of two or more thereof.
[0030] In some embodiments, the preparation method includes: dispersing the multilayer MXene material in a dispersion medium, performing mechanical stress shear exfoliation to obtain a MXene suspension, and centrifuging the MXene suspension at 3000-5000 rpm for 10-30 min to obtain a large-sheet MXene material.
[0031] In some embodiments, the preparation method further comprises: repeating the mechanical stress shear peeling multiple times.
[0032] In some more specific embodiments, the preparation method comprises: 1) Slowly add MAX powder to a mixed solution of HCl and LiF for etching, stir at 50-85°C for 24-72h, and centrifuge to obtain a multilayer MXene precipitate; wherein the mass volume ratio of MAX phase powder, LiF and HCl is (3-10) g: (4.8-16) g: (60-200) mL; wherein the concentration of HCl is 9-12 mol / L; 2) The multilayer precipitate obtained in step 1) was washed twice by centrifugation in 1M HCl, and then washed by centrifugation in water until neutral. During this step, the precipitate was shaken by hand to promote stratification; 3) dispersing the precipitate obtained in step 2) in water and performing mechanical stress shear exfoliation to obtain a MXene suspension; the rotation speed of the mechanical stress shear exfoliation is 500-2000 rpm, and the time is 5-120 min.
[0033] 4) Centrifuging the suspension obtained in step 3) at 3000-5000 rpm for 10-30 min, collecting the black upper layer liquid; Repeating the mechanical stress shearing peeling and centrifuging the remaining multi-layer precipitate for multiple times until no upper layer suspension appears; 5) The black upper layer liquid obtained in step 4) is added in batches into a vacuum coating machine to obtain a single-layer MXene film.
[0034] As another aspect of the technical solution of the present invention, it also relates to a large-sheet MXene material prepared by the aforementioned preparation method, wherein the average lateral size thereof is greater than 4.2 μm.
[0035] As another aspect of the technical solution of the present invention, it also relates to a MXene film, which is formed by the aforementioned large-sheet MXene material.
[0036] In some preferred embodiments, the SSE / t value of the MXene film is 38161 dB–cm 2 –g -1 above.
[0037] In some preferred embodiments, the thickness of the MXene film is 0.1 mm-3 mm.
[0038] As another aspect of the technical solution of the present invention, it also involves the application of the aforementioned large-sheet MXene material or the aforementioned MXene film in the field of electromagnetic absorption and shielding.
[0039] In summary, the present invention proposes a method for exfoliating multilayer MXene by using the rotation of a mechanical stirring paddle to generate uniform shear force, which can efficiently and uniformly obtain high-quality large-scale single-layer MXene, thus facilitating subsequent industrial applications.
[0040] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The reagents and raw materials used in the following examples are commercially available, and the experimental methods without specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.
[0041] Example 1 This embodiment provides a method for preparing a large-sheet MXene material, comprising the following steps: (1) 16 g LiF was added to 200 mL 9 mol / L hydrochloric acid, and then 10 g Ti3AlC2 was added. The mixture was stirred at 50 °C for 24 h for etching, and then centrifuged at 10000 rpm for 2 min to obtain multilayer Ti3C2T x precipitation; (2) The multilayer precipitate was washed twice with 1 M HCl at 10,000 rpm for 2 min, and then washed with water at 10,000 rpm for 2 min until neutral; (3) Multilayer Ti3C2T x The precipitate was dispersed in water and placed in a crescent-shaped paddle mechanical stirrer (the blade diameter was 1 / 2 of the inner diameter of the container) at 1500 rpm for 120 min to obtain Ti3C2T x Suspension; (4) Ti3C2T x The suspension was centrifuged at 3500 rpm for 15 min, and the supernatant was collected.
[0042] The yield of the MXene material prepared in this embodiment is 99.1% (wherein the yield is calculated as: the mass of the obtained single-layer MXene material / the mass of the MAX raw material), and the average lateral size is about 5.3 μm.
[0043] See also Figures 1 to 4 , Figure 1 and Figure 2 The single-layer Ti3C2T prepared in this embodiment is x The SEM images and particle size distribution of MXene show that the products are composed of large single-layer Ti3C2T x composition; Figure 3 The XRD patterns of the raw materials and the products obtained in this example clearly show that all the diffraction peaks of the raw material Ti3AlC2 do not exist in the product, and the diffraction peaks of the product are similar to those of Ti3C2T x be consistent. Figure 4 This is a photo of the MXene material (solution) prepared in large quantities in this example.
[0044] Example 2 This embodiment provides a method for preparing a large-sheet MXene material, comprising the following steps: (1) 16 g LiF was added to 200 mL 10 mol / L hydrochloric acid, and then 10 g Ti3AlC2 was added. The mixture was stirred at 50 °C for 24 h for etching, and then centrifuged at 10000 rpm for 2 min to obtain multilayer Ti3C2T x precipitation; (2) The multilayer precipitate was washed twice with 1 M HCl at 10,000 rpm for 2 min, and then washed with water at 10,000 rpm for 2 min until neutral; (3) Multilayer Ti3C2T x The precipitate was dispersed in water and placed in a crescent-shaped paddle mechanical stirrer (the blade diameter was 1 / 2 of the inner diameter of the container) at 500 rpm for 120 min to obtain Ti3C2T x Suspension; (4) Ti3C2T x The suspension was centrifuged at 3500 rpm for 15 min, and the supernatant was collected.
[0045] The yield of the MXene material prepared in this example is 95.8% (wherein the yield is calculated as: the mass of the obtained single-layer peak MXene material / the mass of the MAX raw material), and the average lateral size is about 6.9 μm.
[0046] See also Figure 5 and Figure 6 , Figure 5 and Figure 6 The single-layer Ti3C2T prepared in this embodiment is x The SEM images and particle size distribution of MXene show that the products are composed of large single-layer Ti3C2T x composition.
[0047] Example 3 This embodiment provides a method for preparing a large-sheet MXene material, comprising the following steps: (1) 16 g LiF was added to 200 mL 10 mol / L hydrochloric acid, and then 10 g Ti3AlC2 was added. The mixture was stirred at 50 °C for 24 h for etching, and then centrifuged at 10000 rpm for 2 min to obtain multilayer Ti3C2T x precipitation; (2) The multilayer precipitate was washed twice with 1 M HCl at 10,000 rpm for 2 min, and then washed with water at 10,000 rpm for 2 min until neutral; (3) Multilayer Ti3C2T x The precipitate was dispersed in water and placed in a crescent-shaped paddle mechanical stirrer (the blade diameter was 1 / 2 of the inner diameter of the container) at 1000 rpm for 120 min to obtain Ti3C2T x Suspension; (4) Ti3C2T x The suspension was centrifuged at 3500 rpm for 15 min, and the supernatant was collected.
[0048] The yield of the MXene material prepared in this example is 98.3% (wherein the yield is calculated as: the mass of the obtained single-layer peak MXene material / the mass of the MAX raw material), and the average lateral size is about 6.1 μm.
[0049] See also Figure 7 and Figure 8 , Figure 7 and Figure 8 The single-layer Ti3C2T prepared in this embodiment is x The SEM images and particle size distribution of MXene show that the products are composed of large single-layer Ti3C2T x composition.
[0050] Example 4 The present invention provides a method for preparing a large-sheet MXene material, comprising the following steps: (1) 4.8 g NaF was added to 60 mL 12 mol / L hydrochloric acid, and then 3 g Nb2AlC was added. The mixture was stirred at 85 °C for 72 h for etching, and then centrifuged at 10000 rpm for 2 min to obtain multilayer Nb2CT. x precipitation; (2) The multilayer precipitate was washed twice with 1 M HCl at 10,000 rpm for 2 min, and then washed with water at 10,000 rpm for 2 min until neutral; (3) Multilayer Nb2CT x The precipitate was dispersed in water and placed in a crescent-shaped paddle mechanical stirrer (the blade diameter was 1 / 2 of the inner diameter of the container) at 2000 rpm for 5 min to obtain Nb2CT. x Suspension; (4) Nb2CT x The suspension was centrifuged at 3500 rpm for 15 min, and the supernatant was collected.
[0051] The yield of the MXene material prepared in this example is 91.5% (wherein the yield is calculated as: the mass of the obtained single-layer peak MXene material / the mass of the MAX raw material), and the average lateral size is about 4.2 μm.
[0052] See also Fig. 9 and Fig.10 , Fig. 9 and Fig.10 The single-layer Nb2CT prepared in this embodiment is x The SEM images and particle size distribution of MXene show that the products are composed of large single-layer Nb2CT x composition.
[0053] Example 5 This embodiment provides a method for preparing a large-sheet MXene material, comprising the following steps: (1) 16 g LiF was added to 200 mL 10 mol / L hydrochloric acid, and then 10 g Ti3AlC2 was added. The mixture was stirred at 50 °C for 24 h for etching, and then centrifuged at 10000 rpm for 2 min to obtain multilayer Ti3C2T x precipitation; (2) The multilayer precipitate was washed twice with 1 M HCl at 10,000 rpm for 2 min, and then washed with water at 10,000 rpm for 2 min until neutral; (3) Multilayer Ti3C2T x The precipitate was dispersed in water and placed in a crescent-shaped paddle mechanical stirrer (the blade diameter was 1 / 3 of the inner diameter of the container) at 1500 rpm for 100 min for stress shear exfoliation to obtain Ti3C2T x Suspension; (4) Ti3C2T x The suspension was centrifuged at 3000 rpm for 10 min, and the supernatant was collected.
[0054] The yield of the MXene material prepared in this example is 94.9% (wherein the yield is calculated as: the mass of the obtained single-layer peak MXene material / the mass of the MAX raw material), and the average lateral size is about 7.0 μm.
[0055] See also Fig.11 and Fig.12 , Fig.11 and Fig.12 The single-layer Ti3C2T prepared in this embodiment is x The SEM images and particle size distribution of MXene show that the products are composed of large single-layer Ti3C2T x composition.
[0056] Comparative Example 1 A method for preparing a MXene material comprises the following steps: (1) 16 g LiF was added to 200 mL 10 mol / L hydrochloric acid, and then 10 g Ti3AlC2 was added. The mixture was stirred at 50 °C for 36 h for etching, and then centrifuged at 10000 rpm for 2 min to obtain multilayer Ti3C2T x precipitation; (2) The multilayer precipitate was washed twice with 1 M HCl at 10,000 rpm for 2 min, and then washed with water at 10,000 rpm for 2 min until neutral; (3) Multilayer Ti3C2T x The precipitate was dispersed in water and placed in a shaker at 2000 rpm for 120 min for vortex shear exfoliation to obtain a monolayer MXene suspension; (4) Ti3C2T x The suspension was centrifuged at 3500 rpm for 15 min, and the supernatant was collected.
[0057] The yield of the MXene material prepared in Comparative Example 1 was 84.8% (wherein the yield was calculated as: the mass of the obtained single-layer peak MXene material / the mass of the MAX raw material), and the average lateral size was about 4 μm.
[0058] Comparative Example 2 A method for preparing a MXene material comprises the following steps: (1) 16 g LiF was added to 200 mL 10 mol / L hydrochloric acid, and then 10 g Ti3AlC2 was added. The mixture was stirred at 50 °C for 24 h for etching, and then centrifuged at 10000 rpm for 2 min to obtain multilayer Ti3C2T x precipitation; (2) The multilayer precipitate was washed twice with 1 M HCl at 10,000 rpm for 2 min, and then washed with water at 10,000 rpm for 2 min until neutral; (3) Multilayer Ti3C2T x The precipitate was dispersed in water and ultrasonically treated in an ice-water bath for 2 h to obtain a monolayer MXene suspension; (4) Ti3C2T x The suspension was centrifuged at 3500 rpm for 15 min, and the supernatant was collected.
[0059] The yield of the MXene material prepared in Comparative Example 2 was 45.8% (wherein the yield was calculated as: the mass of the obtained single-layer peak MXene material / the mass of the MAX raw material), and the average lateral size was about 3.1 μm.
[0060] Comparative Example 3 Compared with Example 2, the difference is that in step (3), the stress shear peeling is carried out in a crescent-shaped paddle mechanical stirrer at 400 rpm for 120 min.
[0061] The yield of the MXene material prepared in Comparative Example 3 was 58.1% (wherein the yield was calculated as: the mass of the obtained single-layer MXene material / the mass of the MAX raw material), and the average lateral size was about 4.3 μm.
[0062] Comparative Example 4 Compared with Example 2, the difference is that in step (3), the stress shear peeling is carried out in a crescent-shaped paddle mechanical stirrer at 2500 rpm for 120 min.
[0063] The yield of the MXene material prepared in Comparative Example 4 was 80.3% (wherein the yield was calculated as: the mass of the obtained single-layer MXene material / the mass of the MAX raw material), and the average lateral size was about 2.2 μm.
[0064] Comparative Example 5 Compared with Example 1, the difference is that in step (3), the stripping is carried out in a propeller-type mechanical stirrer at 1500 rpm for 120 min.
[0065] The yield of the MXene material prepared in Comparative Example 5 was 78.8% (wherein the yield was calculated as: the mass of the obtained single-layer MXene material / the mass of the MAX raw material), and the average lateral size was about 5.2 μm.
[0066] Comparative Example 6 Compared with Example 1, the difference is that in step (3), the stress shear peeling is carried out in a crescent-shaped paddle mechanical stirrer (the blade diameter is 1 / 4 of the inner diameter of the container) at 1500 rpm for 120 min.
[0067] The yield of the MXene material prepared in Comparative Example 6 was 85.0% (wherein the yield was calculated as: the mass of the obtained single-layer MXene material / the mass of the MAX raw material), and the average lateral size was about 5.9 μm.
[0068] As shown in Table 1, the concentration, viscosity, average lateral size, yield and film electromagnetic shielding value of the MXene materials prepared in Examples 1-5 and Comparative Examples 1-6 are compared. Among them, the measurement of electromagnetic shielding is carried out after the MXene film is prepared in batches on a vacuum coating machine. Specifically, 50mL of 20mg / ml MXene solution is vacuum coated and dried at 50°C to obtain a MXene film.
[0069] Table 1: ; As can be seen from the above examples 1-5, the present invention uses a mechanical agitator to utilize continuous concentrated shear force to cause the material to shear and peel under stress, so that it can be quickly layered, thereby obtaining large-layer MXene materials with high yield, wherein the peeling speed is 1500rpm, the time is 120min, and the yield of single-layer MXene can reach 99%. The MXene film obtained by the method of the present invention has good electromagnetic shielding ability, and its SSE / t value can be as high as 41236. Among the current methods, the stripping efficiency of other methods is generally less than 85%, and the SSE / t value of the film is generally less than 30,000. In comparison, the stripping method provided by the present invention achieves high yield and high product quality, and is expected to be put into industrial mass production.
[0070] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0071] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a large-sheet MXene material, characterized in that: include: Etching the MAX phase material with an etchant to obtain a multilayer MXene material; The multilayer MXene material is dispersed in a dispersion medium and subjected to mechanical stress shear exfoliation to obtain a large-sheet MXene material, wherein the average lateral size of the large-sheet MXene material is greater than 4.2 μm.
2. The preparation method according to claim 1, characterized in that: include: The mechanical stress shearing peeling is performed by a mechanical stirring device, wherein the mechanical stirring device comprises a stirring paddle; Preferably, the blade of the stirring paddle is a crescent-shaped blade; Preferably, the diameter of the blade of the stirring paddle is 1 / 3-1 / 2 of the inner diameter of the container; Preferably, the rotation speed of the stirring paddle is 500-2000rpm; Preferably, the mechanical stress shear peeling time is 5-120 min.
3. The preparation method according to claim 1, characterized in that: The MAX phase materials include Ti3AlC2, Ti2AlC, Ti3AlN2, Ti2AlN, Ti3AlCN, Ti4AlN3, Ti2VAlC2, TiVAlC, TiNbAlC, Ti3GeC2, Ti3SiC2, Ti2SnC, V2AlC, V3AlC2, V4AlC3, VNbAlC, VCrAlC, V2GeC, V2GaC, V2ZnC, V2PC, Nb4AlC3, Nb3AlC2, Nb2A1C, Cr2AlC, Cr2GaC, Mo3AlC2, Mo2GaC, Mo2Ga2C, Mo2Ti2AlC3, Mo2TiAlC2, (Mo 2 / 3 Sc 1 / 3 )2AlC、(Mo 2 / 3Y 1 / 3 )2AlC, Ta4AlC3, Ta3AlC2, Ta2AlC, (W 2 / 3 Y 1 / 3 )2AlC、(W 2 / 3 Sc 1 / 3 )2AlC any one or a combination of two or more.
4. The preparation method according to claim 1, characterized in that: include: Adding the MAX phase material to the etchant, stirring at 50-85° C. for 24-72 hours, and centrifuging and washing until neutral to obtain the multilayer MXene material; Preferably, the etchant comprises an acidic solution containing a fluoride salt; Particularly preferably, the fluoride salt comprises any one of LiF and NaF or a combination of both; Particularly preferably, the acidic solution comprises hydrochloric acid; Particularly preferably, the acid concentration in the acidic solution is 9-12 mol / L; Particularly preferably, the mass volume ratio of the MAX phase material, the fluoride salt and the acidic solution is (3-10) g: (4.8-16) g: (60-200) mL.
5. The preparation method according to claim 1, characterized in that: Also includes: The multilayer MXene material is centrifugally washed to neutrality and then dispersed in a dispersion medium; Preferably, the dispersion medium includes any one of water, dimethyl sulfoxide, and N-methylpyrrolidone, or a combination of two or more thereof.
6. The preparation method according to claim 1, characterized in that: include: The multilayer MXene material is dispersed in a dispersion medium, and mechanical stress shear exfoliation is performed to obtain a MXene suspension. The MXene suspension is centrifuged at 3000-5000 rpm for 10-30 min to obtain a large-sheet MXene material.
7. The preparation method according to claim 1, characterized in that: Also includes: The mechanical stress shear peeling is repeated multiple times.
8. The large-sheet MXene material prepared by the preparation method according to any one of claims 1 to 7 has an average lateral size of 4.2 μm or more.
9. A MXene film, characterized in that: The MXene film is formed by the large-sheet MXene material according to claim 8; Preferably, the SSE / t value of the MXene film is 38161 above; Preferably, the thickness of the MXene film is 0.1 mm-3 mm.
10. Application of the large-sheet MXene material according to claim 8 or the MXene film according to claim 9 in the field of electromagnetic absorption and shielding.
Citation Information
Cited By
MXene material and preparation method thereof
CN121536935A
A mxene material and a preparation method thereof
CN121536935B
Large-size MXene-based water-resistant stable adhesive and preparation method thereof
CN122563540A